PENYELESAIAN SENGKETA PERALIHAN HAK ATAS TANAH SUKU PILIANG DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Ilham Saputra; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Every society desperately needs land in its life, in indigenous communities there is a name communal right which is the right of a group of indigenous peoples to a piece of land called communal land. The implementation of this customary right shall be based on the national interest and the state which is not contradictory to other regulations, can be seen in Article 3 of Law Number 5 Year 1960 on the Basic Regulation Agrarian Law and in Article 2 Paragraph (2) of Kampar District Regulation that Function of Land Rights of Ulayat is to improve the welfare of social and economic community members and society and in Kampar custom law regulation any haraus decision based on deliberation to consensus. However, cases that occur in the existence of communal land that is traded / granted and its utilization is no longer in accordance with the existing rules. The purpose of writing this thesis, namely: first, to know the background of the occurrence of Dispute Rights Transfer of Land Piliang Tribe in Kuok Village Kuok District Kampar district, second to know Dispute Settlement Efforts Dispute Rights of Piliang Tribal Land in Kuok Village Kuok Subdistrict Kampar District.This type of research can be classified in the type of sociological research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Kuok Village, Kuok Subdistrict, Kampar District, while the population and sample were all parties related to the problem studied in this study, the data source used primary data and secondary data, data collection technique in this research by interview and literature study.From the results of research, there are three main things that can be concluded. First, because of the daily necessities and different economic interests of indigenous and tribal peoples so that in meeting the needs and interests of the customary law. Secondly, the utilization of communal land is inconsistent with the interests of indigenous peoples and has even caused harm to the indigenous peoples themselves. Third, the dispute settlement is done by chief of the people piliang caniago that seven. The author's suggestion, first, that indigenous peoples should prioritize common interests. Secondly, the management and utilization of communal land should be implemented based. Third, the LAK must perform its of Kuok Kuok Subdistrict, Kampar regency.